Media influence in agriculture practices and scopes for non-chemical agricultural messages - Amalan, A. Adaikalaraj; Aram, I. Arul (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2023)
Non-chemical agricultural methods can improve soil health, conserve ecology and enhance biodiversity, and are more sustainable. Media messages trigger a change in farmers’ attitudes that needs to be studied to understand their practices. This study used the Diffusion of Innovation theory to figure out how farmers accept chemicals in farming practices from the media and how the chemicals impact the environment. The objective is to understand how media influence farmers towards chemical fertilizers and pesticides, to find out which media has been widely used by farmers, and to find out which the popular medium has provided information about non-chemical agricultural methods (NCAM). A stratified sampling technique was used, and fifty small farmers were selected for the survey. The key findings suggested that effective media use by the farmers shift to agricultural practices now and then through media influences on that Non-Chemical Agricultural Methods (NCAM) messages are redefined through survey methodology.